The New Organizational Reality: Downsizing, Restructuring, and Revitalization.
DOI: 10.1037/10252-008
|View full text |Cite
|
Sign up to set email alerts
|

Layoff survivor sickness: What it is and what to do about it.

Abstract: Some of the ideas in this chapter have been discussed by the author in Healing the Wounds: Overcoming the lzauma of Layoffs and Revitalizing Downsized Organizations (Jossey-Bass, 1993) and 'zeadership i n an Age of Lap&" (Issues and Observatrbns, 13131,1993).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 5 publications
(6 reference statements)
1
12
0
Order By: Relevance
“…3 29 Alternatively, feelings of guilt and anger among survivors might act as powerful stressors, reducing employees' resources of coping with an additional stressor, an adverse work environment. 30 A third possible interpretation concerns organisational justice. Several studies show that a low level of organisational justice is associated with reduced health.…”
Section: Discussionmentioning
confidence: 99%
“…3 29 Alternatively, feelings of guilt and anger among survivors might act as powerful stressors, reducing employees' resources of coping with an additional stressor, an adverse work environment. 30 A third possible interpretation concerns organisational justice. Several studies show that a low level of organisational justice is associated with reduced health.…”
Section: Discussionmentioning
confidence: 99%
“…Davy et al (1991) discussed the need for employees to have a stake in the success of their organizations' transition. Noer (1998) described an unquenchable thirst for information that characterized the psychological state of most downsized employees. The experience of downsizing is often chaotic; in the midst of this uncertainty, it is not surprising that employees try desperately to regain some form of control.…”
Section: Discussionmentioning
confidence: 99%
“…In a time ofdownsizing, there is a real need for clear and open communication during all stages of the process (Brockner, 1992;Caudron & Hayward, 1996;Noer, 1998). Cameron et al (1993) suggested that there is a strong need for top-down vision combined with bottom-up input.…”
Section: Discussionmentioning
confidence: 99%
“…Likewise, most of the literature examining survivors has taken a similar view (Brockner et al, 1988). In fact, the term 'lay-oV survivor sickness' has been coined to help describe the common symptoms of guilt, lack of organizational commitment, and fear that survivors often experience following a downsizing (Noer, 1990(Noer, , 1993(Noer, , 1997. Other researchers have used the Kubler-Ross (1969) model to describe survivors' reactions as analogous to the grieving process that occurs after divorce or the loss of a loved one (Newman & Krzysto ak, 1993).…”
Section: Work Transitionsmentioning
confidence: 99%